Genetic Alterations in Benign Breast Biopsies of Subsequent Breast Cancer Patients - Soysal, Savas D.; Ng, Charlotte K. Y.; Costa, Luigi; Weber, Walter P.; Paradiso, Viola; Piscuoglio, Salvatore; Muenst, Simone (Frontiers in Medicine, 2019)
Background: Fibrocystic changes are associated with an increased risk of breast cancer. Genetic alterations have been found in fibrocystic changes with or without epithelial changes, suggesting that critical oncogenic events are occurring at an early stage. Methods: We investigated a unique collective of 17 breast cancer patients who, prior to the diagnosis of invasive breast cancer, underwent open surgical biopsy showing fibrocystic changes of the breast. The time span between biopsy for fibrocystic changes and invasive carcinoma ranged from 1 to 11 years (average 5.3 years). 10 (58.8%) of the patients had an ipsilateral invasive carcinoma, and 7 (41.2%) of the patients developed an invasive carcinoma of the contralateral breast. Massive parallel sequencing targeting genes frequently mutated in breast cancer was performed on the fibrocystic breast tissue as well as the ensuing cancer tissue. Results: In 9 cases, somatic mutations were found in the tumor tissue, the most prevalent being PIK3CA mutations (n=4), followed by TP53 mutations (n=2). None of these mutations were present in the previously removed mastopathy tissue. In one of the cases, an ERBB3 E928G mutation was present in the mastopathy as well as in the tumor tissue, with the variant allele frequency in the mastopathy being <0.1%. In two patients, we found two mutations (MAP3K1 L380fs and PIK3CA I391M respectively) present in the mastopathy as well as in the subsequent breast cancer. These two mutations, however, could also be due to fixation artifacts. Conclusion: Since no significant somatic mutations in the fibrocystic breast tissue, and only doubtful shared mutations between benign and associated cancer tissue were detected, it remains unclear why women with fibrocystic breast disease have a statistically significant increased risk of breast cancer. Further analyses, maybe on the level of gene expression, could help to clarify the role of these benign alterations in the development of breast cancer and help to identify women at greater risk of developing subsequent invasive cancer